Meningkatkan Motivasi dan Kemampuan Menulis Recount Text dengan Metode Picture Series bagi Siswa Kelas VIII-8 - Suaidi, Suaidi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The fact of teaching recount text is currently quite far from the goal. This is the background of the research. Therefore, the picture series method was applied. This study aims to describe and analyze the process of teaching English. The population in this study were all students of class VIII-8 MTs. Negeri 1 Mataram, Mataram City. While the sample in this study were 34 students of class VIII-8 MTs. Negeri 1 Mataram. This type of research is classroom action research (CAR) using a qualitative approach. The data collection techniques for this research are observation, questionnaires, and documentation. The results showed that the teaching and learning process was quite boring and the application of picture series as a teaching method changed the teaching environment. Students become more active and the good impact of this condition is that the evaluation results increase. This is known from the evaluation results starting from the pre-cycle to cycle I and cycle II. The average value of students is 78.00 (did not pass individual and classical), 81.29 (passed individual not classical), and 91.00 (passed individual and classical).